Ternary Composite of Methionine-Functionalized Graphene Oxide, Lanthanum-Doped Yttria Nanoparticles, and Molybdenum Disulfide Nanosheets for Thin-Film Lubrication - Shukla, N.; Verma, D.K.; Singh, A.K.; Kumar, B.; Kavita; Rastogi, R.B. (American Chemical Society, 2020)
For enhancement of the tribological activity of nanolamellar graphene oxide (GO), its nucleophilic substitution was performed by methionine to yield methionine-functionalized reduced graphene oxide (M-rGO). Further, noncovalent functionalization of another tribo active material, nanolamellar MoS2, was accomplished by lanthanum (7%)-doped yttria nanoparticles (NPs), resulting in the formation of a nanocomposite, (La-Y2O3)-MoS2. The doped NPs were deliberately chosen for this purpose because there was a clear increase in the wear/friction-reducing tendencies of yttria after doping with lanthanum. For further advancement of the tribological activity, a ternary nanocomposite (La-Y2O3)-MoS2-(M-rGO) was synthesized containing lanthanum-doped yttria NPs, M-rGO, and MoS2 nanosheets. The NPs, nanosheets, and composites have been characterized by powder X-ray diffraction, high-resolution scanning electron microscopy (HR-SEM), transmission electron microscopy, and Raman spectroscopy. X-ray photoelectron spectroscopy (XPS) was employed to study the chemical states of different elements in (La-Y2O3)-MoS2-(M-rGO). The tribological properties of well-characterized composites were evaluated in paraffin oil (PO) using a four-ball tester according to ASTM D4172 and ASTM D5183 standards at the optimized concentration, 0.20% (w/v). There was incremental evolution in the tribological properties from plain PO through Y2O3, MoS2, M-rGO, La-Y2O3, and (La-Y2O3)-MoS2 and finally to (La-Y2O3)-MoS2-(M-rGO). Here functionalization of GO has invigorated its structure. Both nanosheets coordinated to control agglomeration of the NPs. The NPs prevented the nanosheets from restacking. SEM and atomic force microscopy images of the wear scar validated the results of tribological tests. The presence of yttrium, lanthanum, sulfur, and molybdenum besides carbon, nitrogen, and oxygen in the energy-dispersive X-ray spectrum of the worn surface in the presence of PO blended with (La-Y2O3)-MoS2-(M-rGO) is indicative of its strong adsorption on the surface. On the basis of XPS studies of the wear track, the constituents of the tribofilm could be identified as adsorbed rGO, yttria, lanthanum oxide, and MoS2 in addition to tribochemically produced Fe2O3, MoO3, and SO42-. The mutualistic approach of the constituents has yielded splendid results. © 2020 American Chemical Society.
Keywords: lanthanum-doped yttria nanoparticle; MoS2; functionalized graphene nanosheets; nanocomposite; tribological properties